PERANAN LIURAI DAN RITUAL LISAN DALAM ADOPSI INOVASI USAHATANI SAYURAN MELALUI FARMER FIELD SCHOOL DI TIMOR-LESTE - Gil da Conceicao; Roso Witjaksono (Agro Ekonomi, 2010)
The objectives of research were to (1) understand effect of exsternal and internal factors on farmers activeness in following FFS activities in Sub District Manatuto and Lospalos, (2) explain effects of farmers activeness on following FFS activities on innovation adoption level of vegetables farming. This research used survey method. The respondents were farmers who followed farmer field school in sub District Manatuto and Lospalos (20 administrators and 80 members). Variables used in this research were external factor (role of Liurai, Lisan, agriculture extension and land area) and internal factors (age, frmal and non frmal education, market perception, farmers’ attitude to innovation and motivation) and activeness variables of farmers in following FFS. The results inc=dicated that formal and informal education affected activeness of farmers with sigv=nificant values of 0.034 for formal education and 0.001 for Non formal education. Whie external factors of farmers, namely, role of Liurai, really affected activeness of farmers with significant value of 0.016. furthermore, activeness variables of farmers also really affected level of vegetables farming innovation adoption through FFS in Sub District Mnatuto and Lospalos with significant rate of 0.001.